Effects of Varicocele Repair on Spontaneous First Trimester Miscarriage: A Randomized Clinical Trial - Mandana Mansour Ghanaie (Urology Journal, 2012)
PURPOSE: To evaluate the effects of varicocelectomy on semen parameters, pregnancy rates, and live birth in couples with first term recurrent miscarriage. MATERIALS AND METHODS: One hundred and thirty-six women with recurrent miscarriage were recruited into this study. All of the husbands had normal semen parameters according to World Health Organization criteria and clinical varicocele. In order to evaluate the causes of recurrent pregnancy loss, we looked for chromosomal abnormalities and endocrine, chronic inflammatory, and infectious diseases. Both groups were well matched according to male/female age, varicocele grade, and smoking history. These couples were assigned randomly into two groups: group one (n = 68), in which male partners underwent varicocele repair, and group two (n = 68), which underwent expectant therapy. All of the couples were followed up monthly up to 12 months. All of the women who conceived were followed up until delivery. In each 3-month follow-up visits, two semen analyses were performed. RESULTS: Mean sperm concentration, sperm progressive motility, and sperm with normal morphology improved significantly after elapsing 6 months from varicocelectomy by 75.0%, 15.9%, and 14.3%, respectively, versus the expectant group (P < .01). The overall pregnancy rate was 44.1% and 19.1% within a 12-month period in groups 1 and 2, respectively (P = .003). Of women who conceived in groups 1 and 2, 13.3% and 69.2% developed miscarriage (P = .001). Sperm density/mL (r = 0.072; P = .001), time elapsed from varicocelectomy (r = 0.068; P = .001), and female age (r = -0.062; P = .002) were three most significantly related independent factors to pregnancy rate by multiple regression analysis. CONCLUSION: Varicocelectomy improves semen quality, increases pregnancy rate, and decreases miscarriage rate significantly. Further controlled studies to confirm our results seem warranted.